Medical treatment of advanced cutaneous squamous‐cell carcinoma. (13th December 2019) - Gellrich, F.F.; Hüning, S.; Beissert, S.; Eigentler, T.; Stockfleth, E.; Gutzmer, R.; Meier, F.
Abstract: Considering the rising incidence, cutaneous squamous‐cell carcinoma (cSCC) has a high clinical relevance. In patients with localized cSCC, complete surgical resection is indicated. Radiotherapy should be performed in patients with non‐resectable tumours or in patients who are not suitable for surgery. Systemic therapy is reserved for cSCC that are neither surgically nor radiotherapeutically curable due to their extensive local spread and/or local or distant metastasis. In the absence of prospective randomized phase 3 trials to evaluate and compare the efficacy and safety of chemotherapeutics, epidermal growth factor receptor (EGFR) inhibitors and anti‐PD‐1 antibodies, no final recommendation for systemic therapy can be given for patients with locally advanced or metastatic cSCC. Anti‐PD‐1 antibodies currently show promising results with response rates of up to 50% in both locally advanced and metastatic cSCC. Anti‐PD‐1 antibodies appear to achieve higher response rates compared with EGFR inhibitors, and the duration of response appears to be superior to both chemotherapy and EGFR inhibitors. Compared with chemotherapy, the side effect profile of anti‐PD‐1 antibodies appears to be favourable. Altogether, PD‐1 inhibitors are expected to become the new standard of care for patients with locally advanced and metastatic cSCC. Currently, placebo‐controlled clinical trials are investigating the adjuvant use of cemiplimab and pembrolizumab in patients undergoing resection and radiotherapy of high‐risk cSCC. Patients not eligible for anti‐PD‐1 treatment, e.g. in organ transplant recipients, or in patients refractory to anti ‐ PD ‐ 1 may be offered EGFR inhibitors and/or chemotherapies. Chemotherapies appear to be superior to EGFR inhibitors in terms of response rates, whereas EGFR inhibitors have a more favourable toxicity profile. EGFR inhibitors are therefore more suitable for multimorbid and/or frail elderly patients. By combining EGFR inhibitors with local therapy such as surgery or radiotherapy, response rates and duration of response may be improved.